Pengembangan Media Pembelajaran Powerpoint Interaktif Materi Bangun Datar Untuk Mendukung Merdeka Belajar Siswa di Kelas IV SDN 15 Koto Besar - Ratnawati, Ratnawati; Subhan, Muhammad; Delmayani, Delmayani (Jurnal Ilmiah Dikdaya, 2024)
This research is based on a lack of understanding during the learning process on mastering concepts and not using media that attracts students' attention in learning. This research has the goal of producing interactive powerpoint learning media for grade IV mathematics subjects in the independent curriculum of SDN 15 Koto Besar that is valid, practical and effective.The type of research used is R&D (Research and Development), or development research, with the ADDIE development model, (Analysis, Design, Development, Implementation, and Evaluation). It has several stages of development, the first is analysis, including analysis of needs and characteristics of students. Second, the design of interactive powerpoint preparation. The third development was carried out interactive powerpoint validation tests. The fourth implementation is carried out by practicality test and finally evaluation in the feasibility test of interactive powerpoint products.This development research obtained the results of the validation test by 7 expert validators with an average score of 85.7% of the very valid category, the practicality test was carried out by the class IV guardian with an average score of 91.6% of the very practical category. The results of the trial were seen from the student response questionnaire obtaining an average score of 88.6%. Based on the results obtained, it can be concluded that interactive powerpoints in mathematics subjects in the independent curriculum of grade IV SDN 15 Koto Besar, Valid, and Practical.